Responses of Saccharomyces cerevisiae Cells Grown in Cultures Prepared from Different Tea Infusions to Oxidative Stress - Kirmizikaya, Gorkem; Okutan, Tuba; Kirecci, Oguz Ayhan; Yilmaz, Okkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2023)
Tea is one of the most consumed beverages. Saccharomyces cerevisiae, a model organism in studies on oxidative stress and toxicology, was used to investigate the effects of tea on oxidative stress induced by H2O2. S. cerevisiae cultures were prepared from black, green and white tea infusions and incubated at 30 degrees C for 72 hours. Glutathione-S-transferase enzyme activity and total protein spectrophotometric, malondialdehyde, glutathione and alpha-tocopherol and ergosterol analyses from cell pellets obtained from cultures were performed by HPLC, and fatty acids were performed by GC device. Although protein level in tea infusion groups was higher (p<0.001) compared to control and H2O2 groups, malondialdehyde level decreased (p<0.001). Glutathione and GST levels were decreased in other tea infusion groups except for black tea infusion and black tea infusion+H2O2 groups (p<0.001). Ergosterol levels decreased in both tea infusion and H2O2+tea infusion groups (p<0.05; p<0.001). While palmitic acid increased (p<0.01) in tea infusions and H2O2 groups, palmitoleic acid decreased (p<0.05). Stearic and oleic acid levels decreased in tea infusion groups (p<0.05). As a result, it has been observed that the water-soluble components of tea have effects on fatty acid biosynthesis, other metabolic products and oxidative stress.
Keywords: Glutathione-S-transferase; Hydrogen peroxide; Lipid peroxidation; Saccharomyces cerevisiae; Tea varieties